Long-term care funding in England: An analysis of the costs and distributional effects of potential reforms - Ruth Hancock; Raphael Wittenberg; Bo Hu; Marcello Morciano; Adelina Comas-Herrera (University of East Anglia, Health Economics Group (HEG), 2013)
The UK Government recently announced plans to reform the system that determines how much the state contributes to people's long-term care costs. The reforms will start in 2016 and introduce a lifetime cap on the costs an individual will need to pay towards 'eligible' care and support needs. They will also increase the upper capital threshold above which care home residents are ineligible for local authority help with their care home fees. This increase will extend the possibility of state support to those care home residents who are currently excluded from state help because they have capital, usually including the value of their home, above the current capital threshold of 23,250. The lifetime cap is expected to be 75,000 in 20171, and the upper capital threshold in residential care will be increased to 123,000. This paper examines projected costs and distributional effects of these plans compared with the current system. It also contrasts these costs and distributional effects with the central recommendation of the Commission on the Funding of Care and Support (Dilnot Commission) which was set up by the Government and reported in 2011. The Commission's central recommendation was for a cap of 35,000 and upper capital threshold of 100,000 in 2010 prices. We also consider two variants on the Government's plans which would give additional help to recipients of residential care with capital below the proposed higher capital threshold (see Box 1 for how these compare with the current system, the Government's plans and the recommendations of the Dilnot Commission).
Keywords: H75; I13; I18; 330; long-term care finance; older people; simulation models